Distraction Technique for pain reduction in Peripheral Venous Catheterization: randomized, controlled trial - Balanyuk, Ihor; Ledonne, Giuseppina; Provenzano, Marco; Bianco, Roberto; Meroni, Cristina; Ferri, Paola; Bonetti, Loris (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Procedural pain during Peripheral Venous Catheterization (PVC) is a significant issue for patients. Reducing procedure-induced pain improves the quality of care and reduces patient discomfort. We aimed to compare a non-pharmacological technique (distraction) to anaesthetic cream (EMLA) for the reduction of procedural pain during PVC, in patients undergoing Computerized Tomography (CT) or Nuclear Magnetic Resonance (NMR) with contrast. Methods: This is a Prospective, Randomized Controlled Trial. The study was carried out during the month of October 2015. A total of 72 patients undergoing PVC were randomly assigned to the experimental group (distraction technique, n=36) or control group (EMLA, n=36). After PVC, pain was evaluated by means of the numeric pain-rating scale (NRS). Pain perception was compared by means of Mann-Whitney Test. Results: The average pain in the distraction group was 0.69 (SD±1.26), with a median value of 0. The average pain in the EMLA group was 1.86 (SD±1.73), with a median value of 2. The study showed a significant improvement from the distraction technique (U=347, p<.001, r=.42) with respect to the local anaesthetic in reducing pain perception. Conclusions/Implication for practice: Distraction is more effective than local anaesthetic in reducing of pain-perception during PVC insertion. This study is one of few comparing the distraction technique to an anaesthetic. It confirms that the practitioner-patient relationship is an important point in nursing assistance, allowing the establishment of trust with the patient and increasing compliance during the treatment process.